Comparison between rasterstereographic scan and orthopedic examination for posture assessment: an observational study - Weigel, Samuel; Dullien, Silvia; Grifka, Joachim; Jansen, Petra (Frontiers in Surgery, 2024)
BackgroundAlthough the relationship between posture and back pain is still under debate, the potential role of body alignment highlights the importance of postural assessment in the health sector. Despite growing concern about musculoskeletal issues, there remains a lack of consensus on effective methods for detecting postural anomalies.MethodsThis observational study compared postural assessments conducted by orthopedic specialists with those obtained through rasterstereographical spine scans using the DIERS formetric system. Fifty-four children from the third grade (mean age 9.4 years) underwent both assessments, allowing for a comprehensive examination of orthopedic abnormalities. Statistical analysis, including McNemar tests, was employed to compare the results of the assessments and evaluate potential discrepancies.ResultsThe comparison between the orthopedic examination and the DIERS scan revealed significant differences in assessing trunk imbalance (p < 0.001), thoracic kyphosis (p < 0.001), and lumbar lordosis (p < 0.001). Additionally, the study identified a high prevalence of orthopedic abnormalities, with 79.6% of the examined children exhibiting at least one issue in the orthopedic visual assessment.ConclusionsThe study highlights the divergence between orthopedic evaluations and DIERS scans, emphasizing the challenges in achieving consistent postural assessments. The static analysis provided by the DIERS system, which quantifies posture in angles and distances, contrasts with the dynamic, functionality-focused approach of orthopedic examinations. The findings raise questions about the practicality and significance of integrating rasterstereography into routine pediatric orthopedic practice. The results underscore the complexity of postural evaluations and advocate for a comprehensive approach to address the multifaceted nature of back health in children.